2019
DOI: 10.1371/journal.pone.0226683
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of admitted HIV/AIDS patients in Ethiopian tertiary care settings: A prospective cohort study

Abstract: BackgroundAcquired ImmunoDeficiency Syndrome (AIDS) related illnesses are the leading cause of death in the developing world. However; there is limited evidence regarding the incidence of mortality among admitted HIV patients in Ethiopia.ObjectiveTo determine the incidence of mortality and its predictors among admitted HIV/AIDS patients in selected tertiary care hospitals in Ethiopia.MethodsA prospective cohort study involving 136 admitted HIV/AIDS patients from April 1 to August 31, 2018 was conducted in sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…e common CNS infections identified were cryptococcal meningitis (36.8%), bacterial meningitis (31.6%), and cerebral toxoplasmosis (31.6%). is proportion of CNS infections was consistent with other studies [3,15,20,[28][29][30]. HAART-related toxicity was also among the commonly occurred reasons for hospitalization.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…e common CNS infections identified were cryptococcal meningitis (36.8%), bacterial meningitis (31.6%), and cerebral toxoplasmosis (31.6%). is proportion of CNS infections was consistent with other studies [3,15,20,[28][29][30]. HAART-related toxicity was also among the commonly occurred reasons for hospitalization.…”
Section: Discussionsupporting
confidence: 90%
“…Data on the spectrum of both HIV-and non-HIV-related illnesses that result in hospital admission are essential for policymakers and stakeholders to plan actions in reducing morbidity, mortality, and further hospitalization [14]. Recently, Negera and Mega [15] reported that body mass index (BMI) of less than 18.5 is a significant predictor of inpatient mortality in Ethiopia. However, with the paucity of published data on HIV/AIDS in Ethiopia, little is known about other reasons for hospitalizations, discharge outcomes, and predictors of inpatient mortality in hospitalized patients with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Third, some factors previously associated with adverse outcomes in this population were not analyzed in our study, including socioeconomic (e.g., type of housing, rate of hospital, and emergency unit use), clinical and epidemiological (e.g., weight, intensive care unit stay, and use of non invasive ventilation), and laboratory test characteristics (e.g., lymphocyte count and serum sodium and potassium levels). [18][19][20][21] On the other hand, the present work also has strengths. As far as the authors know, this is the first longitudinal study in southern Brazil, the second among middle and low income countries, to assess the 30-day readmission rate among PLWH.…”
Section: Discussionmentioning
confidence: 89%
“…Ethiopia has the largest population of HIV-infected children in the region. According to an estimate by the Federal HIV/AIDS Prevention and Control Office (FHAPCO), there are over 738,976 people living with HIV/AIDS in Ethiopia [ 3 ]. Of these, 178,500 are children younger than 15 years of age [ 4 ].…”
Section: Introductionmentioning
confidence: 99%